Про можливий варіант інтерпретації укріплення біля села Великі Будки - Корж, А.А. (Археологія і давня історія України, 2021)
На основі інформації попередників, а також власних спостережень, наводиться можливий варіант призначення укріплення біля с. Великі Будки, що у Верхньому Посуллі. Висвітлено просторовий аспект використання та побудови даних захисних споруд. Among the regions of distribution of the settlement sites on the Forest-Steppe of Dnieper Left-Bank area in Ukraine the Sula River basin is one of the least studied meanwhile it is primarily known for its large barrow necropolises. The most famous settlement is Basivka, and others are only briefly mentioned in the professional literature. Scholars do not agree on the purpose of some fortifications. They include the protective structures near Velyki Budky village. Large area, weak cultural layer, as well as the location within the fortified site of the mound necropolis where the height of some barrows is more than six meters, do not speak in favor of the settlement in the classical sense. Also the immediate vicinity of 2 km to the largest site in the region — Basivka settlement which existed since the end of the 6th century BC to the beginning of the 3rd century BC may supplement the above statement. This paper reveals the problem of the fortification interpretation near Velyki Budky village. Favorable topographic location on the cape of the Sula River right-bank which is formed by the confluence of the Khmelivka River gives additional natural protection and shows the strategic importance of the site. Overview of the plain area where the danger was most probable reaches 5—6 km. The author of the paper defends the position of certain «outpost» which protected the path to the weakest point of the Basivka settlement. Therefore, in his opinion, these sites should be considered the single system of fortifications.